Anticancer efficacy of long-term stored plasma-activated medium - Nguyen, Ngoc Hoan; Park, Hyung Jun; Hwang, Soon Young; Lee, Jong Soo; Yang, Sang Sik (Applied Sciences (Switzerland), 2019)
The therapeutic potential of nonthermal atmospheric-pressure plasma for cancer treatment via generation of reactive species, induction of decreased mitochondrial membrane potential, and sequential apoptosis has been reported in our previous studies. Nonthermal atmospheric-pressure plasma-activated medium produced by jetting air plasma above a liquid surface shows advantages over direct plasma such as storage and delivery to tissues inside the body. In this study, we demonstrated that plasma-activated medium can be stored for up to 6 months in a freezer and that the stored plasma-activated medium has anticancer effects similar to those of direct plasma. Plasma-activated medium stored for 6 months showed cytocidal effects on human cervical cancer HeLa cells that were comparable to the effects of fresh plasma-activated medium or direct plasma. Furthermore, the levels of reactive species in plasma-activated medium persisted for up to 6 months. These results indicate that therapeutic application of plasma-activated medium is applicable in plasma medicine and is a promising anticancer strategy.
Keywords: Apoptosis; Plasma-activated medium; Reactive oxygen species